A comparison of HK-CONWIP and BK-CONWIP control strategies in a multi-product manufacturing system. (December 2015) - Onyeocha, Chukwunonyelum Emmanuel; Wang, Jiayi; Khoury, Joseph; Geraghty, John
Abstract: This paper evaluates the performance of the Hybrid Kanban Constant Work-In-Process control strategy and Basestock Kanban Constant Work-In-Process control strategy operating Shared Kanban Allocation Policy (S-KAP) and Dedicated Kanban Allocation Policy (D-KAP) in a multi-product serial flow line. We explored the effect of an increase of product types on the WIP inventory in the system. A simulation-based optimisation technique was used in determining the optimal settings for the strategies. The strategies were compared via pairwise comparison technique and Nelson's ranking and selection procedure. S-KAP responds quicker to demand than D-KAP. BK-CONWIP outperforms HK-CONWIP in a serial manufacturing system. It was shown that an increase in the number of product-type increases the number of PAC and WIP inventory.